The Effect of Using Immediate Feedback on Learning Double Tuck Backflip on Floor Exercises in Artistic Gymnastics For Men Aged 14 – 16 Years Old - Saadi, Ali; Nezar, Tariq (Journal of Physical Education, 2020)
The research aimed at identifying the differences in controlling and experimental groups’ results in posttests of double tuck backflip. The subjects were (8) gymnasts aged (14 – 16) years old divided equally into controlling and experimental groups. All subjects were not able to complete double tuck backflip on floor exercises within artistic performance. The researchers designed an electronic device that is linked to the gymnast body on hip joint to sense the angle between thigh and torso and produce a sound when the angle is acute meaning the performance is correct. If the device does not produce a sound, it means the angle is large or incorrect. The researchers concluded that the immediate feedback device is very useful in learning double tuck backflip shown from the development of the experimental group over the controlling group. Finally, they recommended using this device in learning double tuck backflip as well as learning other skills in the future.